Kombinasi Metode AHP dan TOPSIS pada Penentuan Prioritas Proyek Air Bersih Di Kabupaten Asahan - Maya Lestari; Riki Andri Yusda; Chitra Latiffani (LPPM STMIK Royal Kisaran, 2021)
Abstract: Most of the area in Asahan Regency is a plantation and coastal area where some of the people work as farmers and fishermen. Coastal areas are still lagging behind because they are far from urban areas so that the government pays little attention to it, especially regarding clean water. Clean water in the area can be said to be unfit for use. So that people find it difficult to get clean water for drinking, washing and bathing. These problems can be solved by programs to improve clean water infrastructure and facilities, such as drilling wells and allocating river water, so that they can provide optimal services for clean water, which has a very strong relationship with the economic growth of a region and the socio-cultural life of the community. Determining the priority scale for clean water must look at various criteria so as to produce accurate and precise results. The criteria that are considered in determining the priority of clean water are: Water Condition, Population, Regional Economic Potential, Cost, Level of Interest. To determine the priority of clean water projects at the Public Works and Spatial Planning Office of Asahan Regency, a decision support system is needed that can assist in determining which villages have the right to be prioritized in the priority of clean water projects more effectively and efficiently. Keywords: Clean water; AHP; TOPSIS; Asahan Abstrak: Sebagian Besar Wilayah di Kabupaten Asahan merupakan wilayah perkebunan dan pesisir yang sebagian masyarakatnya bekerja sebagai petani dan nelayan. Di wilayah Pesisir masih tertinggal karena letaknya yang jauh dari perkotaan sehingga kurang diperhatikan oleh pemerintah, terutama mengenai air bersih. Air bersih di wilayah tersebut bisa di bilang tidak layak untuk digunakan. Sehingga masyarakat kesulitan untuk mendapatkan air bersih baik itu untuk diminum, menyuci dan mandi. Masalah tersebut dapat diselesaikan dengan program peningkatan prasarana dan sarana air bersih seperti membuat sumur bor dan pengalokasiam air sungai, agar tetap dapat memberikan pelayanan yang optimal terhadap air bersih memiliki keterkaitan yang sangat kuat dengan pertumbuhan ekonomi suatu wilayah maupun sosial budaya kehidupan masyarakat. Penentuan skala prioritas air bersih tersebut harus melihat dari berbagai kriteria sehingga menghasilkan hasil yang akurat dan tepat. Adapun kriteria yang menjadi pertimbangan dalam penentuan prioritas air bersih ialah: Kondisi Air, Jumlah Penduduk, Potensi Ekonomi Daerah, Biaya, Tingkat Kepentingan. Untuk penentuan proyek prioritas air bersih di Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Asahan maka diperlukan sistem pendukung keputusan yang dapat membantu dalam menentukan desa mana yang berhak didahulukan dalam prioritas proyek air bersih dengan lebih efektif dan efisien. Kata kunci: Air bersih; AHP; TOPSIS; Asahan